2002
DOI: 10.1053/eujp.2001.0311
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect costs of managing patients with musculoskeletal pain—challenge for health care

Abstract: Musculoskeletal pain is an outstanding symptom among the patients of primary health care. However, there are few studies of management and costs of musculoskeletal pain at primary health care level. The aim of this study was to describe the diagnostic investigations, management, referral rate and sick leaves related to visits prompted by musculoskeletal pain as well as to assess their costs. A total of 28 general practitioners (GPs) at 25 randomly selected health centres throughout Finland collected the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
2
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 24 publications
0
61
2
8
Order By: Relevance
“…Recent data suggest that the cost associated with musculoskeletal pain has extensive economic consequences for the community (3,35), and with target estimates of the global burden of musculoskeletal conditions (36) increasing with the aging population, it is essential that appropriate strategies be addressed. Our data suggest that urgent changes need to be made in the understanding and management of joint problems and that a holistic approach to patient care is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that the cost associated with musculoskeletal pain has extensive economic consequences for the community (3,35), and with target estimates of the global burden of musculoskeletal conditions (36) increasing with the aging population, it is essential that appropriate strategies be addressed. Our data suggest that urgent changes need to be made in the understanding and management of joint problems and that a holistic approach to patient care is required.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals reporting such pain represent a considerable direct and indirect cost to health care services (3,4) and are more likely to have poorer general health (5) and greater levels of depression (6), anxiety (7), physical disability (2,8), and associated lost productivity in the workforce (9,10). Although there is some limited recognition that the presentation of multiple joint problems is common (2), the focus of management strategies is still aimed at individual joint problems: indeed, the functional impact on daily tasks of the most common multiple joint combinations has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][9] Rates of health service utilization have been determined, [6][7][8]10 but the economic consequences remain unknown because studies have reported rates rather than costs. In the studies that have reported public costs associated with chronic pain, 8,[11][12][13][14] some components of the costs were not included. None of the studies that measured time lost from employment captured the time that patients and family caregivers devoted to receiving and providing care and time they lost from leisure and household work.…”
Section: Résumémentioning
confidence: 99%
“…Most of the medical measures took place within primary care. More evidence is needed from primary care about the management of musculoskeletal disorders, because this treatment level largely determines the total costs in the long-term perspective (20).…”
Section: Discussionmentioning
confidence: 99%